Reclamation of acid-generating waste rock by in-pit backfilling and sealing : An evaluation of the Kimheden mine site, northern Sweden - Villain, Lucile (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2014)
The notion of mine site reclamation is very recent compared to the history of mining. In thepast, mine sites were left as is following termination of the operations, but modern regulationsrequire anticipation of long-term contamination of the surrounding environment and return ofthe land to a sustainable use. A primary concern for mines used to extract sulphide-rich ores isthe generation of acid mine drainage (AMD), a low-pH and metal-rich solution formed whensulphidic mining wastes and mining surfaces come into contact with oxygen and water. AMDmay be responsible for the contamination of watercourses and other receiving environments fardownstream of the site. Thus, reclamation at such sites will usually involve measures intendedto prevent or mitigate its generation. Despite their relatively recent introduction, the increasingtime that has passed since the first prevention and mitigation programmes were applied at minesites, some two to three decades ago, provides an invaluable opportunity to assess their long-termeffects on the abatement of AMD.Reclamation at the Kimheden copper mine in Västerbotten, northern Sweden, involved theprogressive backfilling of two small open pits with waste rock and application of a dry cover in1996, in order to reduce the influx of atmospheric oxygen into the waste. The objective of thestudies this thesis is based upon, performed in 2009 – 2014, was to evaluate the effects of thesereclamation measures on the abatement of Cu and Zn-rich AMD and to identify potential inadequaciesin them, using geochemical, geophysical and hydrogeological methods.The results show that despite large reductions in Cu and Zn concentrations in the receivingstream following reclamation, its water quality has remained in a steady state for about a decadeand is still not considered satisfactory for discharge into the natural environment. Steady-statemoderately high concentrations in the stream, together with a relatively short turnover time forwater in contact with the waste rock, indicate that sulphide ...